THE EFFECTIVENESS OF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) ON ENGLISH LEARNING OUTCOMES AND STUDENT LEARNING MOTIVATION - Amalia Putri Khusnul Aisyah; Iin Widya Lestari; Khoirul Wafa (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
In this research, Students in the English Education Study Program's eighth semester in 2023/2024 at Nahdlatul Ulama Sunan Giri Bojonegoro will analyze the Student Team Achievement Division (STAD) learning method in order to assess its effects on learning outcomes and student learning motivation. The effect of the STAD method was thoroughly described in this research using a quantitative approach. In this research, 66 students from class X during the academic year 2023–2024 formed into two classes: the experimental class and the control class. Students in the research sample class post-test scores significantly outperformed those in the control class, the research findings showed that the alternative hypothesis (Ha) was accepted. Learning outcomes for students varied both before and after treatment. The experimental class average post-test score was 76.69, while the comparison group's average post-test score was 57.30. Significant (2-tailed) One Way ANOVA post-test values are less than 0.05 or 0.000 0.05. The researcher calculated eta squared to be (0.63 using the effect size statistics using eta squared. A moderate effect size is indicated by the value from eta squared. The average post-test score for the experimental group was 37.79, while the average post-test score for the comparison group was 29.41. showing a considerable improvement in the students' willingness to study. Significant (2-tailed) One Way ANOVA values are less than 0.05 or 0.000 0.05. The researcher discovered from the effect size statistics using eta squared